Dependence of clustering of X-ray AGN on obscuration. Issue 3 (6th September 2018) - Koutoulidis, L; Georgantopoulos, I; Mountrichas, G; Plionis, M; Georgakakis, A; Akylas, A; Rovilos, E
ABSTRACT: Recent studies which select active galactic nucleus (AGN) in the mid-infrared (IR) part of the spectrum find that obscured AGNs reside in more massive dark matter haloes compared to unobscured ones. In contrast, X-ray AGN surveys do not find a difference in the dark matter haloes of these two populations. We visit anew this issue by examining the clustering properties of a large X-ray sample distributed over five deep fields. These are the CDF-N, CDF-S, ECDF-S, COSMOS, and AEGIS Chandra fields spanning the redshift interval 0.6 < $z$ < 1.4. In particular, we present the clustering properties of 736 and 720 unobscured and obscured X-ray-selected AGNs (0.5–8 keV) with column densities higher and lower than $\rm N_H=10^{22}\, cm^{-2}$, respectively. We perform a spatial correlation function analysis for the two samples, and we find a weak (2σ) difference in the clustering of obscured sources ($\rm r_o= 7.0 ± 0.6$ h −1 Mpc) compared to that of unobscured sources ($\rm r_o= 5.4 ± 0.6$ h −1 Mpc) using a fixed slope of γ = 1.8. Furthermore, we compare our findings with recent results that base the obscured and unobscured AGN classification on the optical/IR colour ($R-[4.5]=6.1$ ). We find that the optical/IR criterion fails to identify a purely AGN sample. In particular, reddened AGNs with $R-[4.5]\gt 6.1$ are divided almost equally between X-ray obscured and unobscured AGNs. Derivation of the spectral energy distributions reveals that in many cases the host galaxy contaminates the mid-IR bands thus affecting the optical/mid-IR obscured AGN classification.